(untitled) (Nordic Journal of African Studies, 2010)
The Kîîtharaka causative morpheme (-ith) conveys three readings, a coercive reading, an adversative reading and an assistive reading. This paper argues that these three readings can be captured if it assumed that the causative morpheme itself, as stored in the lexicon, contains the three readings hierarchically ordered, and that whenever there is any of the readings in the syntax, the causative morpheme can be inserted under the superset principle of Nanosyntax (Starke class lectures; Caha, 2007; Starke, 2009).